Health-Related Quality of Life and Its Influencing Factors for Elderly Patients With Hypertension: Evidence From Heilongjiang Province, China - Zheng, Erwei; Xu, Jiao; Xu, Juan; Zeng, Xueyun; Tan, Wan Jie; Li, Jinmei; Zhao, Miaomiao; Liu, Bo; Liu, Rui; Sui, Mingjie; Zhang, Zhong; Li, Yang; et al. (Frontiers in Public Health, 2021)
Abstract Objective Hypertension is one of the most common public health issues worldwide. However, few existing studies examining health-related quality of life (HRQoL) were conducted on elderly patients with hypertension in China. Hence, this study aimed to assess the HRQoL of elderly patients with hypertension and its influencing factors using EuroQol five-dimensional-three-level (EQ-5D-3L) in China. Methods Data were obtained from the 6th National Health Service Survey in Heilongjiang province from June to July 2018, with a stratified multistage random cluster sampling method. All eligible participants were interviewed using a standardized questionnaire, which included the EQ-5D-3L, socio-demographics characteristics, clinical and lifestyle characteristics. The mean EQ-5D index scores for the different subgroups were evaluated using ANOVA. A Tobit regression model was also employed to analyze the potential factors influencing HRQoL. Results A total of 705 elderly patients with hypertension were included in this study. The mean EQ-5D utility score was 0.79 (standard deviation [SD] = 0.23). The proportion of participants reporting pain/discomfort problems was the highest (57.0%), while problems in self-care was the lowest (17.2%). Influencing factors of HRQoL for elderly patients with hypertension included gender, age, income, education level, physical activity, health examination and coexisting diseases. Specifically, the female gender, being above 80 years old, having a lower education and/or higher income, and the presence of coexisting diseases were associated with lower utility index. In contrast, regular physical activity and medical examination had a positive impact on the HRQoL of elderly hypertension patients. Conclusion Overall, elderly patients with hypertension in China have a lower HRQoL than the general population. To improve the HRQoL of elderly patients with hypertension, it is imperative that better public health education is provided to enhance the knowledge of hypertension, encourage the adoption of healthy habits such as regular physical activity and medical examination, and improve the management of coexisting diseases. More care should also be directed to males with hypertension who are above 80 years old.